Study Of Molecular Docking On Compounds With Potential As Anti-Inflammatory - Ravelliani, Andien; Nisrina, Hasna'; Sari, Lala Komala; Marisah, Marisah; Agustin, Annastya Eka; Maharani, Dhavina; Utami, Marsah Rahmawati; Nurfadhila, Lina (Jurnal EduHealth, 2022)
Inflammation is a protective response caused by damage to certain tissues. Anti-inflammatory is a substance or drug used to treat redness, increased body temperature, swelling, pain and loss of function of an organ. Steroid and non-steroidal anti-inflammatory drugs have many side effects, so studies are needed to develop new drugs to minimize side effects and improve therapeutic effects. The method used is literature review from journals and articles obtained from Google Scholar in 15 journals. The purpose of the literature review is to find out the study of the development of new drugs from several compounds that have potential as anti-inflammatories. Secondary metabolites that have potential as anti-inflammatory include essential oils, flavonoids, alkaloids, terpenoids, and anthocyanins. Secondary metabolites will interact with the cyclooxygenase (COX) enzyme which is the main mediator of inflammation. The results obtained from the 15 compounds contain these secondary metabolites so they have the potential as anti-inflammatory.